Injury and Illness Rates During Ultratrail Running - Vernillo, G.; Savoldelli, A.; La Torre, A.; Skafidas, S.; Bortolan, L.; Schena, F. (International Journal of Sports Medicine, 2016)
This study aimed to describe injury/illness rates in ultratrail runners competing in a 65-km race to build a foundation for injury prevention and help race organizers to plan medical provision for these events. Prospectively transcribed medical records were analysed for 77 athletes at the end of the race. Number of injuries/illnesses per 1 000 runners and per 1 000-h run, overall injury/illness rate and 90% confidence intervals and rates for major and minor illnesses, musculoskeletal injuries, and skin disorders were analysed. A total of 132 injuries/illnesses were encountered during the race. The overall injuries/illnesses were 1.9 per runner and 187.9 per 1000-h run. Medical illnesses were the most prominent medical diagnoses encountered (50.3%), followed by musculoskeletal injuries (32.8%), and skin-related disorders (16.9%). Despite the ultra-long nature of the race, the majority of injuries/illnesses were minor in nature. Medical staff and runners should prepare to treat all types of injuries and illnesses, especially the fatigue arising throughout the course of an ultratrail run and injuries to the lower limbs. Future studies should attempt to systematically identify injury locations and mechanisms in order to better direct injury prevention strategies and plan more accurate medical care.
Keywords: dermatological injuries; injury management; musculoskeletal injuries; trail running; ultraendurance; ultramarathon